Relationship between chest CT manifestations and immune response in COVID-19 patients. (September 2020) - He, Susu; Zhou, Chao; Lu, Dongqing; Yang, Haihua; Xu, Hailing; Wu, Guixian; Pan, Weijia; Zhu, Rui; Jia, HaiJian; Tang, Xinni; Chen, Xi; Wu, Xiaomai
Highlights: The absolute values of CD3+, CD4+, and CD8+ T cells are lower in COVID-19 patients. The levels of IL-6 and IL-10 are increased in COVID-19 patients. The absolute values of CD4+ T cells are decreased in COVID-19 patients. The severity of lung lesions predicts poor clinical outcomes. CT signal may be a predictor of the transition from mild to severe. Abstract: Objectives: To study the correlations of lymphocytes and cytokines between changes of lung lesion volumes in patients with COVID-19, and to predict these correlations. Methods: 93 patients with COVID-19 were divided into mild and severe groups. The data of lymphocyte subgroups and cytokines were collected, the imaging characteristics were measured, and correlation analysis was performed to analyze the differences. Results: 60 mild and 33 severe patients were included. Lymphocyte subsets decreased in both groups. The reduction percentages of the absolute lymphocytes value in mild and severe groups were 32% and 64%, respectively. The lung CT lesion volume of all patients was 241.45 ± 282.92 cm 3, among which the mild group was 151.29 ± 226.04 cm 3, and the severe group was 405.38 ± 304.90 cm 3, respectively. In critically ill patients, the decrease of the absolute value of CD4+ T cells and the increase of IL-6 levels are significantly correlated with the volume of lung lesions. Conclusions: The absolute values of CD3+, CD4+, and CD8+ T cells are lower in patients with COVID-19, while the levels of IL-6 and IL-10 are increased. The severity of lung lesions predicts poor clinical outcomes and may be a predictor of the transition from mild to severe.